Epidemiological Analysis of Influenza A Infection in Cambodian Pigs and Recommendations for Surveillance Strategies. Issue 5 (25th January 2014) - Netrabukkana, P.; Cappelle, J.; Trevennec, C.; Roger, F.; Goutard, F.; Buchy, P.; Robertson, I.D.; Fenwick, S.
Summary This study analysed the available data of seroprevalence to human influenza viruses in pigs in Cambodia using generalized linear mixed models in order to improve understanding of factors underlying the spread of human influenza viruses in Cambodian pigs. The associations between seroprevalence against seasonal H1N1 influenza virus in pigs and the population density of humans and pigs were not significant. However, a positive association between anti‐H3 antibodies in pigs and the human population density was identified. In contrast, there was a negative association between seroprevalence of H3N2 in pigs and the pig population density. Our study has highlighted the difficulty in identifying epidemiological risk factors when a limited data set is used for analyses. We therefore provide recommendations on data collection for future epidemiological analyses that could be improved by collecting metadata related to the animals sampled. In addition, serosurveillance for influenza A viruses in pigs in high‐risk areas or at slaughterhouses is recommended in resource‐limited countries.